The eschatology of 1 Thessalonians in the light of its spirituality - P. G. R. de Villiers (Acta Theologica)
This article investigates the eschatology of 1 Thessalonians from the perspective of its spirituality. It first analyses the way in which eschatology suits and reflects its Thessalonian context and the conversion of the Thessalonians. Secondly, it analyses how past events are presented in light of their final spiritual journey. Thirdly, it describes the present situation in Thessalonica and, fourthly, the future in terms of God’s ultimate soteriological and judicial actions for humanity. The article concludes with a discussion of the mystical nature of eschatology and the specific pronouncements about the future transformation of believers.